Sustainability Objective of Tourism Industry Investment in Original Income Recovery in Indonesia - Loo, Petrus (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2022)
The purpose of this study is to explain whether directly or indirectly the variables of economic growth and the regional minimum wage (UMR) on original income in Indonesia (GDP) through the variable amount of investment in the tourism sector. In this study, the independent variable is the variable of economic growth and the regional minimum wage (UMR), while the dependent variable is original income in Indonesia (GDP) and the intervening variable is the variable amount of investment in the tourism sector. The data obtained in this study are data on Indonesia's economic growth, Indonesian UMR data, Indonesian GDP data and investment data in the tourism sector for 2016-2020 using the path analysis method. The research method used in this study is a quantitative descriptive research method using path analysis with Based on the results of research analysis, the conclusion of this study is that partially the economic growth and UMR variables have a significant effect on the GDP variable and the investment variable in the tourism sector. Simultaneously, the variables of economic growth and the minimum wage have an effect on the GDP variable through the investment variable in the tourism sector. Through the results of research that has been stated that good economic growth, data will increase good GDP, where economic growth and increased GDP, economic growth and increased GDP will be able to increase investment in tourism, where this investment will indirectly increase GDP in tourism and will boost economic growth. If the UMR increases, it will increase productivity, so that it will be able to increase GDP and at the same time boost economic growth, and vice versa if the UMR does not increase, then productivity will decrease and GDP will decrease and this will result in a decrease in economic growth.